Progression of chronic lower limb ischemia in a patient with occlusion of the infrarenal aorta after myocardial revascularization using the internal thoracic artery: a clinical case - R. N. Lar'kov; R. V. Shilov; P. G. Sotnikov; S. S. Zagarov; Yu. Yu. Kolesnikov; K. V. Petrakov; M. Yu. Kazanskii; M. V. Vishnyakova; R. Yu. Nikonov; G. A. Mirzemagomedov (Alʹmanah Kliničeskoj Mediciny, 2019)
Background: The main cause of mortality in patients with atherosclerosis of aorta and peripheral arteries of the lower extremities is ischemic heart disease. The presence of peripheral artery atherosclerosis suggests a high probability of simultaneous coronary involvement. To reduce the risk of cardiac complications, these patients are offered myocardial revascularization as the first step of the intervention; however, the choice of a conduit for coronary artery bypass in these patients remains challenging.Case report: A 58-year old man with combined coronary artery stenoses, high occlusion of the aorta and common iliac arteries underwent autoarterial myocardial revascularization with the right internal thoracic artery (ITA) and left radial artery ("off pump”). In the early postoperative period, significant progression of the right leg ischemia was observed, related to partitioning of the main collateral flow between the right ITA and the inferior epigastric artery, that had contributed to blood supply to the right lower extremity. Taking into account the lack of efficacy of medical treatment and progression of the leg ischemia, at day 4 postoperatively the patient underwent resection of the infrarenal aorta with aortobifemoral bypass grafting and restoration of blood supply to the lower extremities and resolution of ischemia.Conclusion: ITA has been recognized as the conduit of choice for surgical treatment of ischemic heart disease; however, its use may result in significant progression of ischemia. When choosing a conduit, ITA at the side of less ischemic lower extremity is preferred. ITA imaging by computed tomography-angiography or by selective ITA angiography can be helpful for assessment of the ITA significance at the side of less ischemic leg. Also, the appearance of retrograde flow in the inferior epigastric artery at Doppler ultrasound examination can be a conditional valuable criterion.